TINGKAT KESEJAHTERAAN KELUARGA PENARIK BECAK MOTOR DI TENGAH PANDEMI COVID-19 - Habibah, Astri; Ritonga, Fajar Utama (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
Motorized rickshaw pullers are jobs in the informal sector in the transportation sector. Working as a motorcycle rickshaw puller does not require special skills, it's just being able to ride a motorcycle. Motorcycle rickshaw pullers have been classified as poor people because of the decreasing number of customers due to many people who already have their own vehicles and are getting more and more difficult during the COVID-19 pandemic. The purpose of this study was to determine the impact of the COVID-19 pandemic on the welfare level of motorcycle rickshaw drivers where the presence of the COVID-19 pandemic made it difficult for rickshaw drivers to get passengers because schools and train stations which are usually places to look for passengers were closed. However, motorized rickshaw pullers must continue to work in the midst of the COVID-19 pandemic in order to earn income. This type of research is classified as descriptive research with a qualitative approach to see the level of welfare of motorized rickshaw pullers in the midst of the COVID-19 pandemic. Data collection methods used are interviews, observation and literature study. Sources of data used are primary data in the form of interviews and observations and secondary data in the form of literature study. This study found that the level of welfare of a family who pulled a motorcycle rickshaw in the midst of the COVID-19 pandemic based on indicators from the BBKBN showed that the level of welfare was classified as a pre-prosperous family by taking into account several aspects such as income, food, clothing, housing, health, education, and savings. Due to COVID-19, the income of a family who pulls a motorcycle rickshaw is sometimes not enough to meet the needs of daily life